Obstructive jaundice as the initial manifestation of hepatocellular carcinoma in a patient with previously unknown chronic hepatitis B infection: a case report and literature review - Blanco, Joaquin; Gonzalez, Luis D.; Cortes, Abigail; Jimenez, Nidia; Pavia, Mario R.; Gutierrez, María X. (International Journal of Research in Medical Sciences, 2024)
Hepatocellular carcinoma (HCC) is the most common liver neoplasm, accounting for 90% of cases, with hepatitis B and C infections being the main risk factors for its development. Diagnosis is primarily based on imaging studies, serology, and histology. Clinically, it presents with right upper quadrant pain and B symptoms, with jaundice occurring in 19-40% of cases. However, the onset of obstructive jaundice as the initial symptom occurs in approximately 1-12% of cases. We present the case of a 65-year-old male with a recent diagnosis of diabetes mellitus, who presented with progressive jaundice, documenting suggestive imaging findings of hepatocellular carcinoma with portal involvement and a positive viral panel for hepatitis B. Pathology report confirmed a differentiated hepatocellular carcinoma.